2020
DOI: 10.1248/bpb.b19-00838
|View full text |Cite
|
Sign up to set email alerts
|

Induced Prostanoid Synthesis Regulates the Balance between Th1- and Th2-Producing Inflammatory Cytokines in the Thymus of Diet-Restricted Mice

Abstract: Multiple external and internal factors have been reported to induce thymic involution. Involution involves dramatic reduction in size and function of the thymus, leading to various immunodeficiency-related disorders. Therefore, clarifying and manipulating molecular mechanisms governing thymic involution are clinically important, although only a few studies have dealt with this issue. In the present study, we investigated the molecular mechanisms underlying thymic involution using a murine acute diet-restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…Moreover, EP1 agonists in vitro promote Th1 responses [ 45 ], while PGE2 in vivo induces Th17 cell differentiation, as well as the production of pro-inflammatory cytokines [ 46 ]. On the other hand, inhibition of COX-2 by non-steroidal anti-inflammatory drugs inhibits the development of Th1 and Th2 lymphocytes [ 47 ]. Moreover, in vitro COX-2 inhibition reduces B cell maturation and antibody production, with EP2 and EP4 receptors playing the most important role in the process as their agonists affect B cell activation [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EP1 agonists in vitro promote Th1 responses [ 45 ], while PGE2 in vivo induces Th17 cell differentiation, as well as the production of pro-inflammatory cytokines [ 46 ]. On the other hand, inhibition of COX-2 by non-steroidal anti-inflammatory drugs inhibits the development of Th1 and Th2 lymphocytes [ 47 ]. Moreover, in vitro COX-2 inhibition reduces B cell maturation and antibody production, with EP2 and EP4 receptors playing the most important role in the process as their agonists affect B cell activation [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brain levels of PGE 2 and its metabolites, 15k-PGE 2 and dhk-PGE 2 , were measured by LC-MS/MS essentially as described elsewhere 51 . In brief, the brain samples were homogenized with methanol and solid phase extraction was performed using Oasis HLB extraction cartridges (Waters Corporation, Milford, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Accumulated evidence supports the idea that stress leads to an increase of pro-inflammatory cytokines (Li et al 2016(Li et al , 2020. However, the data from animal models and clinical research revealed significant variabilities in type I and type II cytokine profiles (Cuervo et al 2021;Koivisto et al 2019;Razali et al 2020). It seems to be clear that the examination of a single cytokine or small groups of cytokines is not sufficient to evaluate the alterations of cytokines in depression-related animal models.…”
Section: Effects Of Nai Exposure On Cytokine Levels Of Cms-treated Micementioning
confidence: 99%